Association of psychiatric morbidity with quality of life among late adolescent girls: exploring the iceberg - R., Narayana Murthy M.; C., Smitha M.; Ram, Dushad; Kulkarni, Praveen; C., Ashok N. (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescents constituting major chunk of the population, though seem to be healthy group, and are affected by various ailments among which mental disorders constitutes considerable proportion which often begins in adolescence is both preventable and treatable. Less described in the literature is the association between quality of life and a wide range of psychopathology in adolescents especially among girls and henceforth this study was conducted to determine the association between psychiatric disorders and quality of life among late adolescent girls. Methodology: This cross-sectional study was conducted in a randomly selected pre-university and degree college in Mysore city, Karnataka, India for a period of one year among adolescent girls 16-19 years. Sample size estimated was 683. Mini international neuropsychiatric interview, Version 6.0 was used to diagnose psychiatric morbidity and WHOQOL BREF Questionnaire was used to collect data on Quality of life. Data collected was analyzed using SPSS V.22 .Proportions was calculated, Mann-Witney U Test was used to see the association of psychiatric morbidity with Quality of life. Binary logistic regression was used to determine the independent predictability of psychiatric morbidity by various domains of quality of life. Results: Analysis showed that overall prevalence of mental health disorders was found to be 15.5 % with major depressive disorder being the most common accounting to 37% There was significant association seen between psychiatric disorder with overall quality of life and physical, psychological, social and environmental domains of QOL (p<0.05). On binary logistic regression overall quality of life was found to be independent predictor of psychiatric morbidity. Conclusion: Overall quality of life was found to be independent predictor of psychiatric morbidity.